ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI KERJA PEGAWAI DI PUSKESMAS PASAR MATANGGOR KABUPATEN PADANG LAWAS UTARA - Elly Rikayanti; Mappeaty Nyorong; Nuraini Nuraini (Jurnal Kesehatan dan Fisioterapi, 2023)
An effective HR management can create a work environment that provides a sense of togetherness, supports productivity, and encourages members to work towards achieving goals. This research aims to analyze what factors are related to employee work motivation in the work area of the Pasarmatanggor Community Health Center, North Padang Lawas Regency. This research is a quantitative research with a research design using the Analytical Survey method with a Cross Sectional approach. The research was conducted in the work area of the Pasarmatanggor Community Health Center, North Padang Lawas Regency from September to October 2021. The total sample was 71 employees. The data in this research includes primary data, secondary data and tertiary data. Data analysis was carried out using univariate analysis tests, bivariate analysis using the Chi-square test and multivariate analysis using the logistic regression test. The research results showed that in the univariate analysis of 71 respondents, the majority of respondents aged 36-45 years, namely 35 (49.3%) respondents, had worked for 1-5 years, namely 36 (50.7%) respondents, had a level of D3 education, namely 40 (56.3%) respondents. In the bivariate analysis it is known that there is a relationship between supervision and employee work motivation, there is a relationship between working conditions and employee work motivation, there is a relationship between appreciation and employee work motivation. In the multivariate analysis, there are variables that Abstrak are most related to employee work motivation in the work area of the Pasarmatanggor Community Health Center, North Padang Lawas Regency. Based on the results of this research, it is recommended that policy makers take action related to implementing employee work in accordance with education in North Padang Lawas Regency.Keywords: Supervision, Working Conditions, Rewards, Work Motivation